A hybrid analytical-numerical algorithm based general modeling framework of molecular diffusivity in cement paste. (December 2021) - Gao, Yun; Wu, Kai; Rong, Zhidan; Yuan, Qiang
Highlights: The XCT and MIP tests provide a quantitative description of pore structure. A general modeling framework of molecular diffusion is proposed. A two-level hybrid analytical-numerical algorithm is implemented. Abstract: Diffusion phenomena such as the ingress of various deleterious ions are of crucial importance to the service life of reinforced concrete. A physical parameter, i.e., the molecular diffusion coefficient or diffusivity is often used to define the diffusion rate. To date, the determination of molecular diffusivity remains a challenging issue, though numbers of laboratory tests and modeling methods have been developed. This paper is to present a general modeling framework of molecular diffusivity in cement paste. The necessary inputs come from the usual tests of X-ray computed tomography and mercury intrusion porosimetry, while a two-level hybrid analytical-numerical algorithm is proposed. At the voxel level, a general expression of modified Archie's equation is derived upon a combination of tortuosity model and fractal theory. At the cement paste level, a finite element method is adopted for the sake of homogenization. It is shown that the general modeling framework can be a good alternative to predict the molecular diffusivity in cement paste from the knowledge of structural feature as determined through experiments.